Control approach to the load frequency regulation of a Generation IV Lead-cooled Fast Reactor. (October 2015) - Ponciroli, Roberto; Cammi, Antonio; Lorenzi, Stefano; Luzzi, Lelio
Highlights: Dedicated control strategy for adjusting the electrical power according to the grid requirements. Decoupling of the Balance of Plant from the reactor primary circuit thanks to effective feedback regulators. Primary frequency regulation and islanding simulations assessed with an object-oriented model. Abstract: One of the most pressing issues in the study of the power generation and distribution is the characterization of the grid behavior, whether a relevant fraction of the connected power plants relies on Renewable Energy Sources. Indeed, because of the discontinuous power supply and the limited presence of energy accumulators, concerning power imbalances may take place on the grid. The power plants ensuring high reliability performance should be ready to feed the loads when the Renewable Energy Sources are not available. In order to ensure the grid stability and the sustainability of nuclear energy, the possibility of operating Generation-IV nuclear reactors in a flexible way should be considered, i.e., the Nuclear Power Plants should adjust the mechanical power produced so as to comply with the sudden grid frequency variations. In the present work, this opportunity is assessed for the Lead-cooled Fast Reactors, adopting the Advanced Lead Fast Reactor European Demonstrator (ALFRED) as a representative of Lead-cooled Fast Reactor technology. For this reactor concept, because of the large thermal inertia that characterizes the system, the adoption of the "reactor-follows-turbine" scheme (currently employed in the Pressurized Water Reactors) is not feasible. An alternative solution is proposed, i.e., the set-point for the thermal power produced in the core is kept constant at the nominal value (or slowly variable), and the set-point for the mechanical power available to the alternator is adjusted according to the load demands. In order to assess the performance of the developed control scheme, two case studies are simulated. In the first one, a frequency profile of the synchronous Continental European grid is provided. In the second simulation, the possibility of performing the islanding operational transient is evaluated. Such an operational transient needs the connected power plants to perform relevant power variations in few seconds in order to deal with the abrupt change in the grid powered configuration. The simulation outcomes show that the proposed control scheme allows achieving prompt mechanical power variations. As for the quantitative results, in both simulations the frequency value is maintained below the upper safety threshold (50.8 Hz). On the other hand, the control scheme complies with the technological constraints set for the safe operation of the primary circuit of the ALFRED reactor. In particular, the Balance of Plant pressure-induced feedbacks on the primary circuit dynamics are effectively dampened, i.e., the temperature in the cold leg is effectively maintained close to its set-point (i.e., 400 °C) and the plant is almost insensitive to the variations of the grid power demands.